EXTRACTION, FRACTIONATION, AND SEPARATION OF CYNAROSIDE AND SCOLYMOSIDE FROM Cynara scolymus L. GROWN IN IRAQ - Mohammed M. Farhan; Dhia S. Hassawi; Nabeel K. Ibraheem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Artichoke (Cynara scolymus L.) is a nutritious vegetable that grown all over the world. It is a promising herbal plant, rich in bioactive components. It is considered as medicinal plant due to its nutritional and phytochemical composition, especially high proportion of phenolic compounds. The primary aim of this study was to achieve chemical profile analyses of artichoke for different phytochemcials, especially Scolymoside and Cynaroside. Methanolic crude was extracted from Artichoke leaves by rotary evaporator and separated by column chromatography. The fractions monitored by Thin Layer Chromatography (TLC), and identified in High-Pressure Liquid Chromatography (HPLC). Two important compounds, Scolymoside and Cynaroside were separated and identified. In overall, Artichoke could be regarded as a rich source of biologically active compounds and considered as bio-functional with putative antioxidant effects.